Does Information about Personal Emissions of Carbon Dioxide Improve Individual Environmental Friendliness? A Survey Experiment - Yamashita, Hideki; Kyoi, Shinsuke; Mori, Koichiro (Sustainability, 2021)
The purpose of this study is to identify factors that can change the environmental friendliness of individuals in the context of climate change issues in terms of values, beliefs, controllability, concern, attitude, intention, and behavior through a survey experiment, and to test the hypothesis that providing information about the amount of carbon dioxide (CO2) emissions attributable to an individual with its threshold value motivates him/her to reduce that amount using statistical analyses (the Mann–Whitney test) and multivariate regressions (the ordered logit model). It is crucial to change the behavior of individuals as well as organizations to reduce the emissions of CO2 for solving climate change issues, because the aggregate amount of individual CO2 emissions is too large to ignore. We conducted a survey experiment to detect factors affecting the environmental friendliness of individuals. Subjects of the experiment were 102 students at Shiga University in Japan. They were randomly provided with communication opportunities, information about individual or group CO2 emissions, and information about their threshold value. The finding is that provision of information about the amount of individual and group CO2 emissions may be able to improve that person’s environmental friendliness in terms of values, beliefs, concern, attitude, intention, and behavior.